Combination of Advanced Platelet-Rich Fibrin and Pentoxifylline/Tocopherol as a Novel Preventive Option in Osteoradionecrosis: A Case Report - Vorakulpipat, Pasinee; Suphangul, Suphachai; Fuangtharnthip, Pornpoj; Ghanaati, Shahram; Vorakulpipat, Chakorn (European Journal of Dentistry, 2022)
Osteoradionecrosis (ORN) of the jaws is an uncommon complication of radiation therapy that seriously affects the oral and maxillofacial region. Management of ORN is intrinsically difficult and treatment effects are unpredictable. ORN can be treated with pentoxifylline/tocopherol and autologous platelet concentrates to promote wound healing. Furthermore, the low speed of relative centrifugal forces platelet-rich fibrin (PRF + ) has been shown high efficacy for ORN. A 72-year-old male patient with history of radiation treatment for squamous cell carcinoma in the left side of the tongue. Six years after the treatment, his upper right first molar tooth (no. 16) was surgically extracted due to persistent pain. A few months following the extraction, intraoral examination showed gingival inflammation, and pain when palpation around the edentulous area of tooth no. 16. Radiological examination revealed retained root of 16 with radiolucent area and horizontal bone loss around upper right second molar tooth (no. 17). Pentoxifylline and tocopherol were given for a week before the surgical operation and were continued for 8 weeks after the operation. Retained roots of teeth no. 16 and 17 were removed and the sockets were debrided, the advanced PRF+ (A-PRF + ) membranes were placed followed by primary wound closure. Following 2 weeks of treatment, the mucosa healed and progressed to complete mucosal coverage at 2 months with no pathological findings or ORN progression. At 6-month follow-up, clinical and cone-beam computed tomography (CBCT) revealed no pathology. Our case demonstrates that the combination of pentoxifylline/tocopherol and the A-PRF+ surgical approach can be useful for wound healing and prevention of ORN.
Keywords: osteoradionecrosis; bone defect; bone regeneration; platelet-rich fibrin; pentoxifylline; tocopherol